The realm of the public sphere (identity and policy) Vol.3 - Rudolph, Lloyd I.; Rudolph, Susanne Hoeber (New Delhi, 2008)
This volume is the third of the three volumes that collect the Rudolphs' life works over a period of fifty years since their first visit to India in 1956. Volume III comprises four parts: Identity Politics, Interpreting Lives: Gandhi and Amar Singh, Making US Foreign Policy, and Writing as Public Intellectuals. The five essays in the first section, Identity Politics, discuss caste and the politics of identity as a dominant category in the Indian political scenario. In the four essays in the second section, Interpreting Lives: Gandhi and Amar Singh, the Rudolphs address their central concern, that is, the method, validity, and scope of subjective knowledge available from first person narratives such as an autobiography or a diary. In the five essays in the third section, Making US Foreign Policy, the authors address the causes of regional instability in South Asia; how US policy impacts the South Asia region; and the interaction of foreign and domestic politics. The nine essays in the last section, Writing as Public Intellectuals, are distinguished from academic writing and were written to influence thought and opinion in the American public sphere.
Keywords: Democracy